Long-term effects of infliximab on bone and cartilage turnover markers in patients with rheumatoid arthritis. Issue 3 (20th July 2007) - Chopin, F; Garnero, P; le Henanff, A; Debiais, F; Daragon, A; Roux, C; Sany, J; Wendling, D; Zarnitsky, C; Ravaud, P; Thomas, T
Abstract : Background: Rheumatoid arthritis (RA) is associated with systemic bone loss, subchondral bone erosion and cartilage degradation under the control of pro-inflammatory cytokines, including tumour necrosis factor α (TNFα). Therefore, we tested the hypothesis that administration of infliximab, an anti-TNFα drug in the treatment of RA, would modulate systemic and local bone resorption and reduce cartilage degradation. Methods: We performed a prospective study of a multicentric cohort of 48 women, mean (SD) age 54.2 (12.1) years old, with severe RA for 11.4 (7.8) years, who started infliximab after failure of other disease-modifying antirheumatic drugs. At baseline and 6, 22 and 54 weeks after initiating Infliximab therapy we measured the following biochemical markers: pro-collagen serum type I N-terminal propeptide (PINP), a marker of bone formation; serum C-terminal cross-linked telopeptide of type I collagen (CTX-I), a marker of cathepsin K-mediated bone collagen degradation believed to reflect systemic bone resorption; serum C-terminal cross-linked telopeptide of type I collagen (ICTP), an index of matrix metalloprotease (MMP) mediated type I collagen degradation reflecting preferential joint metabolism; and urinary CTX-II a biochemical markers of cartilage degradation. Total hip and lumbar spine bone mineral density (BMD) was assessed at baseline, and after 6 and 12 months by dual-energy x-ray absorptiometry (DXA). No patient received bisphosphonates while 77% were under oral glucocorticoids. Results: BMD remained stable over 1 year. Serum CTX-I levels rapidly decreased by 19% and 28% at week 6 and week 22, respectively (analysis of variance (ANOVA) p = 0.032) values returning to pre-treatment level at week 54. By contrast, ICTP levels progressively declined with a maximal 25% decrease at week 54 (ANOVA p = 0.028). By contrast, PINP levels remained stable over time, which led to a 30 to 40% improvement in bone remodelling balance, as assessed by the ratios PINP/CTX and PINP/ICTP (p<0.05). There was no significant change of urinary CTX-II in the whole population, but a slight decrease (ANOVA p = 0.041) in those with pre-treatment levels above the upper limit of normal range. Conclusions: In summary, the improvement in the formation/resorption marker ratio suggests beneficial systemic and local bone effects of infliximab in patients with RA.